Palladium‐Catalyzed Cascade Carbonylation to α, β‐Unsaturated Piperidones via Selective Cleavage of Carbon–Carbon Triple Bonds. Issue 41 (6th September 2021) - Ge, Yao; Ye, Fei; Yang, Ji; Spannenberg, Anke; Jiao, Haijun; Jackstell, Ralf; Beller, Matthias
Abstract: A direct and selective synthesis of α, β‐unsaturated piperidones by a new palladium‐catalyzed cascade carbonylation is described. In the presented protocol, easily available propargylic alcohols react with aliphatic amines to provide a broad variety of interesting heterocycles. Key to the success of this transformation is a remarkable catalytic cleavage of the present carbon–carbon triple bond by using a specific catalyst with 2‐diphenylphosphinopyridine as ligand and appropriate reaction conditions. Mechanistic studies and control experiments revealed branched unsaturated acid 11 as crucial intermediate. Abstract : A catalytic carbonylative cleavage of carbon–carbon triple bonds is achieved. This allows for a general and direct synthesis of α, β‐unsaturated piperidones by palladium‐catalyzed cascade carbonylation of alkynols.